Sosialisasi Pencegahan Korupsi dan Penguatan Integritas Aparatur Pemerintah Desa - Bambang Sasmita Adi Putra; Ali Azhar; Feni Puspita Sari; Gushairi; Didi Syaputra; Herdiansyah; Jamri; Triyana Syahfitri (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2025)
This Community Service activity aims to enhance legal awareness and integrity of village government officials through anti-corruption socialization. Conducted in Desa Pintasan, Kecamatan Gaung, Kabupaten Indragiri Hilir, the activity employed a participatory approach using interactive lectures, discussions, and case studies. The results indicate an increased understanding among village officials regarding the limits of authority, accountability principles, and legal consequences of administrative actions that may violate regulations. Furthermore, the socialization successfully instilled values of integrity and transparency in village governance. The activity also provided a platform for dialogue between village officials and academics, fostering a more contextual understanding of law implementation in everyday governance practices. These findings highlight the importance of legal literacy as a preventive strategy in fostering clean, accountable, and sustainable village administration. Practically, the activity strengthened village officials’ capacity to prevent corrupt practices and improve public service quality. From an academic perspective, the results provide important empirical evidence on the effectiveness of participatory approaches in enhancing the integrity of village government officials.